Relationship between corporate social responsibility (CSR) and internationalisation strategies: A descriptive study in the Spanish context - José-Luis Godos-Díez; Laura Cabeza-García; Cristina Fernández-González (Administrative Sciences, 2018)
Corporate social responsibility (CSR) is a voluntary competitive strategy that is based upon social, economic, and environmental improvement in which the organisation is involved. Internationalisation, a type of corporate strategy, is a set of processes that help companies to expand globally to achieve the aim of improving their competitive position. Both of the strategies have become more important due to ever increasing globalisation, whose consequences modify economic and business environments, thus causing them to be more dynamic and competitive. This directly affects business management, thus companies increasingly consider the opinion of society, attempting to gain stakeholders' trust through effective CSR management. In this context, this paper aims to analyse CSR and internationalisation strategies and their possible connection from a theoretical viewpoint. From a practical viewpoint, the relationship between both strategies is analysed while using a sample of Spanish listed companies.
Keywords: 350; CSR; Internationalisation; Strategic management